Trend analysis of production dynamics agricultural products - Kostyshyn, О.; Dudych, L. (Land Management, Cadastre and Land Monitoring, 2023)
The research is devoted to the trend analysis of the dynamics of production in agricultural sectors as a tool for forming an optimal program of their functioning in order to establish trends and forecast their further development, as well as to evaluate the method of trend analysis in relation to the scope of its application in the research of agricultural sectors. It is substantiated that the forecasting of economic indicators is possible along trend lines, if their parameters, in particular the approximation coefficient R2 and the correlation coefficient R ensure the necessary reliability of the forecast data. An assessment of the possibility and expediency of applying the technique of horizontal analysis - trend analysis and selection of a trend line was carried out. It was established that when studying the economic indicators of the Lviv region, such as the production of all agricultural products and plant products, the correlation coefficient provides such reliability (1 ≤ R ≥ 0.95), but for the livestock industry, it does not (R=0.56 ). When studying the economic indicators of the crop industry as a whole in Ukraine, such as the production of rapeseed (R=0.74), soybean (R=0.67) and wheat (R=0.48), it was established that the corresponding correlation coefficients do not provide the necessary reliability for forecasting trend lines for the economic forecast of the development of agricultural industries.Key words: trend line, dynamics, time series, agricultural production, wheat, rapeseed, soybeans.
Keywords: trend line; dynamics; time series; agricultural production; wheat; rapeseed; soybeans.